Analisis Komparatif Kinerja Keuangan Perbankan Syariah Menggunakan Metode Camels pada Sebelum, Selama dan Sesudah Krisis Global Tahun 2008 - Suci Kurniawati (Journal of Accounting and Investment, 2012)
In 2008 the global financial crisis that hit the United States has spread to the whole world. Conditions of the global economic crisis affecting the financial performance of banks and each bank has the financial performance of the condition varies in receiving the impact of global crisis include Shariah banking. Thus the purpose of this study was to determine the comparison and test the differences between the financial performance of Shariah banking, objects used in this study is the bank Syariah Mandiri and Bank Muamalat Indonesia and Bank Syariah Mega Indonesia in the period 2007, 2008, 2009 using the method CAMELS. The study was based on the rating of the CAMELS method that uses a Bank Indonesia Regulation 9/1/PBI/2007. The study was a quantitative study using a comparative description and analysis of secondary data collection methods in the form of annual financial statements of each Islamic bank and the sampling method using a purposive sampling method. Data were processed using SPSS and data analysis performed using One Way ANOVA. The results showed that the overall ratio of otherwise healthy banks in the years 2007-2009 CAMELS BSM and BMI, and BSMI has an average level of health in the composite ranking categories. Based on the results obtained there was no significant difference between the performance of CAMELS in BMI, BSM and BSMI. At the time of global crisis Bank Syariah Mandiri is superior to preserve the value and growth ratio compared Muamalat Indonesia and Bank Syariah Mega Indonesia.